Synthesis, Spectroscopic Characterization, Structural Studies, and in Vitro Antitumor Activities of Pyridine-3-carbaldehyde Thiosemicarbazone Derivatives - Hernández Gorritti, Wilfredo Román (2020)
Eight new thiosemicarbazone derivatives, 6-(1-trifluoroethoxy)pyridine-3-carbaldehyde thiosemicarbazone (1), 6-(4'-fluorophenyl)pyridine-3-carbaldehyde thiosemicarbazone (2), 5-chloro-pyridine-3-carbaldehyde thiosemicarbazone (3), 2-chloro-5-bromo-pyridine-3-carbaldehyde thiosemicarbazone (4), 6-(3',4'-dimethoxyphenyl)pyridine-3-carbaldehyde thiosemicarbazone (5), 2-chloro-5-fluor-pyridine-3-carbaldehyde thiosemicarbazone, (6), 5-iodo-pyridine-3-carbaldehyde thiosemicarbazone (7), and 6-(3',5'-dichlorophenyl)pyridine-3-carbaldehyde thiosemicarbazone (8) were synthesized, from the reaction of the corresponding pyridine-3-carbaldehyde with thiosemicarbazide. The synthesized compounds were characterized by ESI-Mass, UV-Vis, IR, and NMR (1H, 13C, 19F) spectroscopic techniques. Molar mass values and spectroscopic data are consistent with the proposed structural formulas. The molecular structure of 7 has been also confirmed by single crystal X-ray diffraction. In the solid state 7 exists in the E conformation about the N2-N3 bond; 7 also presents the E conformation in solution, as evidenced by 1H NMR spectroscopy. The in vitro antitumor activity of the synthesized compounds was studied on six human tumor cell lines: H460 (lung large cell carcinoma), HuTu80 (duodenum adenocarcinoma), DU145 (prostate carcinoma), MCF-7 (breast adenocarcinoma), M-14 (amelanotic melanoma), and HT-29 (colon adenocarcinoma). Furthermore, toxicity studies in 3T3 normal cells were carried out for the prepared compounds. The results were expressed as IC50 and the selectivity index (SI) was calculated. Biological studies revealed that 1 (IC50¿=¿3.36 to 21.35¿µM) displayed the highest antiproliferative activity, as compared to the other tested thiosemicarbazones (IC50¿=¿40.00 to >582.26¿µM) against different types of human tumor cell lines. 1 was found to be about twice as cytotoxic (SI¿=¿1.82) than 5-fluorouracile (5-FU) against the M14 cell line, indicating its efficiency in inhibiting the cell growth even at low concentrations. A slightly less efficient activity was shown by 1 towards the HuTu80 and MCF7 tumor cell lines, as compared to that of 5-FU. Therefore, 1 can be considered as a promising candidate to be used as a pharmacological agent, since it presents significant activity and was found to be more innocuous than the 5-FU anticancer drug against the 3T3 mouse embryo fibroblast cells.